Nonlinear dust-acoustic wave propagation in a Lorentzian dusty plasma in presence of negative ions. (22nd October 2018) - Denra, Raicharan; Paul, Samit; Ghosh, Uttam; Sarkar, Susmita
Abstract : In this paper we have studied the effect of the density and temperature of negative ions on the nonlinear dust-acoustic wave propagation in a Lorentzian dusty plasma. We have considered both adiabatic and non-adiabatic dust charge variation. The presence of both low and high populations of negative ions are considered. Separate models have been developed because the two populations give rise to opposite polarity of grain charges. In both models electrons are assumed to follow a kappa velocity distribution while the positive and negative ions satisfy a Maxwellian velocity distribution. Adiabatic dust charge variation shows the propagation of a dust-acoustic soliton in cases of both a high and low population of negative ions whose amplitude depends on the negative ion temperature and negative ion density. On the other hand, non-adiabatic dust charge variation generates a stable oscillatory dust-acoustic shock when the negative ion population is low. An unstable potential has been predicted from this analysis when the negative ion population is high and the dust charge variation is non-adiabatic.